Tick-borne encephalitis in domestic animals - Salát, Jiří; Růžek, Daniel (Acta virologica, 2020)
Tick-borne encephalitis (TBE), a disease caused by tick-borne encephalitis virus (TBEV), represents a serious neural infection of humans in Europe and Asia. The main reservoir hosts of TBEV are ticks, rodents and insectivores, but domestic animals may also be infected with the virus. This review summarizes what is known about TBE in domestic species (e.g., dogs, horses), in which infection may manifest with clinical signs similar to those seen in severe human cases. We also focus on TBE in ruminants where TBE infections are typically asymptomatic and do not cause health problems in the infected hosts. However, the risk to human health is the main problem of asymptomatic infection, because the presence of TBEV in the milk of infected ruminants can serve as a source of TBE infection via the alimentary route. An experimental veterinary vaccine was developed recently, and future vaccination of selected domestic animals is proposed to avoid the development of severe TBE symptoms in sensitive animals (e.g., dogs, horses) or to decrease the risk of alimentary infection in humans (e.g., goats and sheep).
Keywords: klíšťová encefalitida; Animals, Exotic; Horses; lidé; hospodářská zvířata; Encephalitis, Tick-Borne; nemoci koní; mléčné výrobky; nemoci psů; vakcinace; Food Contamination; Vaccination; Viral Zoonoses; Foodborne Diseases; Humans; přežvýkavci; psi; viry klíšťové encefalitidy; exotická zvířata; Ruminants; zvířata; kontaminace potravin; koně; Encephalitis Viruses, Tick-Borne; Animals, Domestic; Dogs; Animals; Horse Diseases; nemoci přenášené potravou; Dairy Products; virové zoonózy; Dog Diseases